Medical education as a necessitate for field force - Noushad , Shamoon; Ahmed , Sadaf; Ahmed , Faiza (International Journal of Endorsing Health Science Research, 2015)
Caregivers are important escort in the healing journey of any patient. Our country in last decades excel so much in terms of offering training programes for nurses and midwives to bridge the gap between the therapeutic interventions and knowledge of these working individuals. We have done a survey on 182 nurses both male and female working in specifically small towns and trust hospitals. They were interviewed about their skills and the duties allocated to them. With reference to the patient care and conditions they were inquired about the medical background and awareness of the sufferer’s ailment. We have found nearly disappointing results as almost 71% of these workers were ignorant of the fact that they lack basic knowledge of related medical conditions of concerned patients. Rest of the data also gave the evidence for a huge breach among the awareness, education and realistic approach in this selected workforce. We suggest that caregivers must be aware of indications and have strong medical foundation of the concerned departments where they are serving. We propose the medical education and clinical workshops for this set of serving individuals at ground levels along with the technical fine tuning with the help of case studies and practice. We recommend to improve this field force especially who are serving the majorities and in rural areas.